2018
DOI: 10.1016/j.phytol.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial prenylated stilbenoids from peanut (Arachis hypogaea)

Abstract: Stilbenoids are a class of secondary metabolites with a stilbene backbone that can be produced by peanut (Arachis hypogaea) as defence metabolites. Six monomeric prenylated stilbenoids, including the compound arachidin-6 (4), were isolated from extracts of fungus-elicited peanuts (Arachis hypogaea) using preparative liquid chromatography. Their structures were confirmed by MS n , HRMS and NMR spectroscopy and their antibacterial activity was evaluated against methicillin-resistant Staphylococcus aureus (MRSA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Novel chemical scaffolds with different modes of action to currently used antibiotics are constantly being investigated 7 . Prenylated flavonoids and isoflavonoids, collectively termed as (iso)flavonoids, as well as stilbenoids, have shown promising antibacterial activity against clinically-relevant pathogens, including MRSA 8 , 9 . Prenylated phenolic compounds are a class of secondary defence metabolites produced by species of the Fabaceae family upon (a)biotic stress 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Novel chemical scaffolds with different modes of action to currently used antibiotics are constantly being investigated 7 . Prenylated flavonoids and isoflavonoids, collectively termed as (iso)flavonoids, as well as stilbenoids, have shown promising antibacterial activity against clinically-relevant pathogens, including MRSA 8 , 9 . Prenylated phenolic compounds are a class of secondary defence metabolites produced by species of the Fabaceae family upon (a)biotic stress 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with their role as phytoalexins, peanut prenylated stilbenoids have been shown to accumulate upon challenge with microorganisms [142][143][144][145]149] and to possess remarkable antifungal activity [150][151][152]. Several recent studies have shown interesting therapeutic potential for peanut prenylated stilbenoids [135,136,153,154]. Prenylated compounds generally exhibit greater bioavailability than their non-prenylated counterparts, due to the increase in lipophilicity linked to the prenyl groups.…”
Section: Prenylationmentioning
confidence: 99%
“…1,710 As a result of their health benefits, prenylated flavonoids are currently investigated as potential biopharmaceuticals and functional foods. Last but not least, prenylated (iso)flavonoids have also received interest because of their promising antimicrobial activity, 1114 suggesting that they might also be used as food preservatives or antibiotics in clinical applications.…”
Section: Introductionmentioning
confidence: 99%